2001
DOI: 10.1149/1.1359194
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemistry of InSb as a Li Insertion Host: Problems and Prospects

Abstract: Ballmilling of In and Sb has been used to produce InSb for use in electrochemical and in situ X-ray diffraction studies ͑XRD͒ of Li/1 M LiPF 6 ethylene carbonate:diethyl carbonate/InSb cells. The cell capacity decays rapidly when cycled between 0 and 1.3 V, while the capacity reduction is less pronounced when cycling is restricted to the 0.65-1.4 V range. In situ XRD studies reveal that Li 3 Sb and In are formed during the first plateau ͑above 0.65 V͒, according to the reaction 3Li ϩ InSb → Li 3 Sb ϩ In. The i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
113
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(130 citation statements)
references
References 6 publications
16
113
1
Order By: Relevance
“…In atoms are extruded beyond this concentration of Li, leading to very little further volume expansion. These results show best agreement with the experimental conclusions of Tostmann et al 12 The maximum number of intercalated Li atoms before In extrusion as reported by Hewitt et al 10 is almost half the value obtained in the present work. According to the energetics, the compound Li 2 InSb is unstable, but if formed leads to an enormous volume expansion of 15.4%.…”
Section: A Lithiation Of Insb and Cu2sbsupporting
confidence: 94%
“…In atoms are extruded beyond this concentration of Li, leading to very little further volume expansion. These results show best agreement with the experimental conclusions of Tostmann et al 12 The maximum number of intercalated Li atoms before In extrusion as reported by Hewitt et al 10 is almost half the value obtained in the present work. According to the energetics, the compound Li 2 InSb is unstable, but if formed leads to an enormous volume expansion of 15.4%.…”
Section: A Lithiation Of Insb and Cu2sbsupporting
confidence: 94%
“…This means that Li 2 Sb is not re-formed during delithiation. The second lithiation shows two plateaus again, but the first one is now observed at *0.89 V and probably still corresponds to the equilibrium between Sb and Li 2 Sb [116], which has been seen before using in situ XRD [117].…”
Section: Antimonysupporting
confidence: 60%
“…8 shows the cyclic voltammetry (CV) curves of product Sb5 in the initial three cycles. The reversible electrochemical reaction formula in lithium ion battery can be described as the lithium alloying/de-alloying in antimony [54][55][56]:…”
Section: Electrochemical Performance Of Sb/c Composite Fibersmentioning
confidence: 99%